(untitled) (Research, Society and Development, 2021)
Despite the benefits provided by Concept Maps (MCs) in the teaching and learning process, it is clear that this tool is often little known and used in the classroom by Basic Education teachers. Thus, this article aimed to evaluate and reflect on the application of a didactic action on MCs and CmapTools, for basic education teachers, in order to promote and expand knowledge about these pedagogical support tools. The action involved a participatory activity structured in four stages: i) Application of the initial questionnaire; ii) Dialogical exposition on the Theory of Meaningful Learning and Concept Maps; iii) Demonstrations on the operation of CmapTools; and iv) Application of the final questionnaire. The data obtained through the questionnaires and records of spontaneous reports placed revealed a lack of participants in these pedagogical elements addressed, but, at the same time, there was a great interest in the topic associated with the desire to obtain more theoretical and practical insights into the MCs and its use in the classroom.